Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Low-moisture extrusion exerts distinct effects on the dynamic digestion kinetics of proteins in plant-based meat analogues - Zi Chen; Aiqian Ye; Tiantian Sun; Yiming Zhao; Weilin Liu; Jianzhong Han; Quanquan Lin (Food Research International, 2026)

Alnustone ameliorates obesity and polycystic ovary syndrome by remodeling adipose metabolism via AMPK signaling - Yiming Qin; Shourui Hu; Yanqi Xu; Zongxuan Lin; Xiaofan Liang; Yue Liu; Yuxuan Li; Chunxuan Geng; Xiangyan Chen; Xizi Feng; Zi-Jiang Chen; Han Zhao; et al. (Science China Life Sciences, 2026)

Is BPA only the tip of the iceberg? Occurrence and risk assessment of 32 bisphenol analogues in landfill leachate - Zhi-Zhong Zhang; Lin-Hui Zhang; Hang Li; Fei Chen; Sakhayana Nikolaevna Danilova; Ming-Han Li; Bing-Feng Liu; Yi-Fan Li; Zi-Feng Zhang (Journal of Hazardous Materials, 2026)

An adaptor protein CRK mediates antiviral immunity against white spot syndrome virus via JAK/STAT signaling pathway in Cherax quadricarinatus - Zi-Han Fan; Ling-Ke Liu; Wen-Lin Wu; Hai-Peng Liu (Fish & Shellfish Immunology, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Arching patterns in compacted clay: insights from plane-strain trapdoor tests - Xiang-Shen Fu; Han-Lin Wang; Zi-Jian Zhai; Ren-Peng Chen; Daniel Dias (Transportation Geotechnics, 2026)

Evolutionary mechanism of passive soil arching effect in sand at various relative densities and heights of fill - Han-Lin Wang; Zi-Jian Zhai; Xiang-Shen Fu; Xiao-Hu Zhang; Daniel Dias; Ren-Peng Chen (Transportation Geotechnics, 2026)

Structural reconstruction-induced electronic Kagome lattices with low-energy flat bands in twisted double bilayer graphene - Mo-Han Zhang; Yalei Zhang; Chen-Yue Hao; Zi-Han Guo; Chao Yan; Ya-Xin Zhao; Ya-Ning Ren; Jin-Hua Gao; Shengjun Yuan; Lin He (Science Bulletin, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Particle size distribution (PSD) of mine waste dump via unmanned aerial vehicle (UAV) image recognition and sieving - Han Ke; Zi Han Lin; Xiao Fei Wei; Bing Zhou; Tian Shou Hu; Shuai Zhang; Jie Hu; Chen Sheng Zhang (Engineering Geology, 2025)

Distinct responses of fungal and bacterial denitrification genes to seasonal changes, nitrogen deposition and precipitation reduction in subtropical forest soils - Qirun Chen; Fengyi Han; Maokui Lyu; Zhiwei Zeng; Yanjiang Cai; Yuheng Cheng; Zi-Yang He; Milin Deng; Jinsheng Xie; Yongxin Lin (Applied Soil Ecology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

A new collapse mechanism of RC frame structures under earthquakes: Shaking table tests and numerical analysis - Zhe Xu; Zi-Han Chen; Feng Lin (Soil Dynamics and Earthquake Engineering, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Hysteresis elongation behavior of RC beams failing in different modes: Experimental investigation and numerical modelling using smeared crack approach - Zi-Nan Wu; You Dong; Xiao-Lei Han; Jing Ji; Jing-Cong Lin (Engineering Structures, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Comammox Nitrospira and ammonia-oxidizing bacteria are metabolically active in a subtropical estuarine wetland - Mengmeng Feng; Yongxin Lin; Guiping Ye; Zi-Yang He; Dong Zhu; Hang-Wei Hu; Yuheng Cheng; Fengyi Han; Ping Yang; Ji-Zheng He (Applied Soil Ecology, 2025)

Comparative analyses of bacterial contamination and microbiome of broiler carcasses in wet market and industrial processing environments - Yuanyuan Zhou; Nan-lin Wang; Jin-qi Cen; Jia-tong Han; Yu-xuan Tang; Zi-qi Xu; Hang Zeng; Kurt Houf; Zhongjia Yu (International Journal of Food Microbiology, 2025)

In-situ forming flame-retardant gel polymer electrolyte through Ritter reaction: An innovative strategy for enhancing the safety of lithium metal battery - Si-Xin Jia; Tian-Qi Xiang; Zi-Han Zhang; Jian-Jun Zhou; Lin Li (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

High-rate pig manure substitution enhances comammox Nitrospira abundance and diversity in the Cinnamomum camphora coppice planting soils - Luyuan Sun; Jie Zhang; Jia Liu; Jiao Zhao; Ting Zhang; Fengyi Han; Zi-Yang He; Yongxin Lin (European Journal of Soil Biology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Co-occurrence of elevated arsenic and fluoride concentrations in Wuliangsu Lake: Implications for the genesis of poor-quality groundwater in the (paleo-)Huanghe (Yellow River) catchment, China - Ya-Ni Yan; Jun-Wen Zhang; Na Wu; Zi-Han Xia; Lin Liu; Zhi-Qi Zhao (Water Research, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Air permeability variation of compacted loess: effects of soil basic properties and dry-wet cycles - Shi-Feng Lu; Xiao-Pei Guo; Xing-Rui Wang; Zi-Jing Han; Ling Xu; Xiao-Lin Huang; Lu Zuo (Bulletin of Engineering Geology and the Environment, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Post-stroke Chinese pure alexia: linguistic features and neuropsychological profiles - Shen-yi Kuang; Yi Xu; Yu-yuan Wang; Zi-gao Wang; Qiang Dong; Xiang Han; Shi-Lin Yang (Acta Neurologica Belgica, 2024)

Fermented Syzygium samarangense leaves mitigate oxidative stress-triggered hepatotoxicity through Nrf2 activation and epigenetic regulation - Ssu-Han Huang; Zi-Han Lin; Tien-Yuan Wu; Guor-Jien Wei; Yen-Chen Tung; Zheng-Yuan Su (Food Bioscience, 2024)

Re-evaluating the impact and mechanism of digital economy on regional pollution intensity from the perspective of spatial spillover - Pei-Ling Yang; Zi-Han Lin; Zhen-Ning Zhu; Feng-Wei Ying (Environmental Science and Pollution Research, 2024)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Effects of synthetic astaxanthin and Haematococcus pluvialis on growth, antioxidant capacity, immune response, and hepato-morphology of Oncorhynchus mykiss under cage culture with flowing freshwater - Wei Zhao; Han-Lin Wei; Meng-Die Chen; Rong Yao; Zi-Qiao Wang; Jin Niu (Aquaculture, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Efficiently immobilizing uranium (VI) by oxidized carbon foam - Hongliang Bao; Chunyu Xie; Ling Han; Zenghui Yue; Yuan Qian; Linjuan Zhang; Zi-Jian Li; Huangjie Lu; Jian Lin; Jian-Qiang Wang (Environmental Science and Pollution Research, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

MtDNA-Based Phylogeography of the Red Alga Agarophyton vermiculophyllum (Gigartinales, Rhodophyta) in the Native Northwest Pacific - Kai-Le Zhong; Xiao-Han Song; Han-Gil Choi; Shimada Satoshi; Florian Weinberger; Stefano G. A. Draisma; De-Lin Duan; Zi-Min Hu (Frontiers in Marine Science, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Species diversity and distribution of the genus Colpomenia (Scytosiphonaceae, Phaeophyceae) along the coast of China - Xiao-Han Song; Zi-Min Hu; Zhong-Min Sun; Stefano G. A. Draisma; Pablo Fresia; De-Lin Duan (Algae, 2019)

Circular RNAs exhibit extensive intraspecific variation in maize - Zi Luo; Linqian Han; Jia Qian; Lin Li (Planta, 2019)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Oceanic currents drove population genetic connectivity of the brown alga Sargassum thunbergii in the north‐west Pacific - Jing‐Jing Li; Zi‐Min Hu; Xu Gao; Zhong‐Min Sun; Han‐Gil Choi; De‐Lin Duan; Hikaru Endo (Journal of Biogeography, 2017)
Aim Oceanic currents are among the most pervasive hydrodynamic features in shaping community dynamics, population connectivity and phylogeographical structure of intertidal species. Here, we test whether population structure and biogeographical gradients of genetic diversity in the brown alga Sargassum thunbergii are correlated with oceanic currents in the north‐west Pacific ( NWP ). Location North‐west Pacific (25.07°N–43.36°N). Methods Nuclear internal transcribed spacer‐2 and mitochondrial cox 3 sequences were obtained from 835 and 810 individuals of S. thunbergii respectively. Parsimony networks and phylogenetic trees (maximum parsimony and Bayesian inference) were constructed to evaluate phylogeographical structure. Pairwise F ST estimates and analyses of molecular variance ( AMOVA ) at various hierarchical levels (latitude, longitude, marine provinces, biogeographical basins and zoogeographical zones) were conducted to elucidate population genetic differentiation. migrate software was used to estimate the number of migrants between adjacent populations. Results Several lines of evidence indicate that S. thunbergii is characterized by shallow population structure. Geographical distances do not correlate with population pairwise genetic differentiations. The corridor/stepping‐stone model‐based coalescent analyses reveal high levels of asymmetric gene flow among S. thunbergii populations, with the numbers of migrants largely corresponding to the directions of oceanic current systems in the NWP . Genetic signatures also indicate that Jeju Island, Korea might act as a transition zone for dispersal of S. thunbergii in the NWP driven by the Kuroshio Current, thus facilitating subsequent transportation northward into the Sea of Japan and the Yellow‐Bohai Sea. Main conclusions Population genetic homogeneity in S. thunbergii was mainly structured by oceanic currents rather than palaeoclimatic events. Our study illustrates an important phylogeographical case of how coastal hydrodynamic factors contributed to population connectivity and geographical shifts of genetic diversity for marine organisms without a pelagic stage.

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.